RANCANG BANGUN SISTEM MONITORING KINERJA PANEL SURYA BERBASIS MIKROKONTROLLER ATMEGA 328 - Dede Pramana, Dewa Gede; Arta Wijaya, I Wayan; Arsa Suyadnya, I Made (Jurnal SPEKTRUM; Vol 4 No 2 (2017): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2017.v04.i02.p12, 2018)
This research aims to develop a system capable of monitoring the performance of solar panels. This design is based on microcontroller atmega 328. In making this system is divided into two parts, namely, the design of hardware (hardware) which consists of the design of electronic devices. Second, the design of software (software). Programming of monitoring and recording system using Microsoft visual basic and arduino IDE software. Testing results using 12v light emitting diode (LED), monitoring system has been able to inform if the solar panel there is a voltage drop in the presence of an indicator on the sides of the panel, if the voltage is below the minimum 8v, then on the red panel panel lights up the indicator is not good, otherwise it will turn green if the voltage above the minimum voltage limit is 8v and the status is good. The results of software testing have been successful showing the expected results at the time of testing using black box testing method.